Pulmonary Complications as Predictors of Weaning Outcomes in Myasthenic Crisis: A Systematic Review and Meta-analysis - Rossyana Dewi, Putri; Surya Atmaja, Kadek; Widyantara, I Wayan; Harry Pranata, I Made (Syntax Corporation, 2026)
Pulmonary complications are common during invasive mechanical ventilation in myasthenic crisis and may significantly influence extubation success. Although pneumonia, ventilator-associated pneumonia (VAP), and atelectasis are frequently reported, their quantitative association with weaning outcomes has not been systematically evaluated. The research aims to determine whether pneumonia/VAP and atelectasis are associated with poor weaning outcomes—including extubation failure, prolonged mechanical ventilation, or difficult weaning—in patients with myasthenic crisis. This systematic review and meta-analysis followed PRISMA 2020 guidelines and was registered in PROSPERO. Comprehensive searches of MEDLINE, Embase, Scopus, and CENTRAL were conducted through January 2025. Observational studies in adult myasthenic crisis were included. Risk ratios (RRs) were pooled using a random-effects model; risk of bias was assessed with ROBINS-I, and evidence certainty with GRADE. Of 1,246 records, 934 were screened after deduplication; 60 full-texts assessed; 4 studies included. Pneumonia/VAP was significantly associated with poor weaning outcomes (RR = 1.78, 95% CI 1.41–2.24; = 3%). Atelectasis showed a nonsignificant trend (RR = 1.28, 95% CI 0.93–1.75; = 35%). Evidence certainty was moderate for pneumonia/VAP and low for atelectasis. Publication bias was unassessable due to few studies. Pneumonia and VAP substantially increase extubation failure and weaning difficulties in myasthenic crisis. Atelectasis's role remains inconclusive. Aggressive pulmonary infection management may improve outcomes; prospective studies are needed